2016
DOI: 10.1074/jbc.m116.714485
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Signaling Pathways Controlled by LRP1 (Receptor-related Protein 1) Cytoplasmic and Extracellular Domains Limit Cellular Cholesterol Accumulation

Abstract: The low density lipoprotein receptor-related protein 1 (LRP1) is a ubiquitously expressed cell surface receptor that protects from intracellular cholesterol accumulation. However, the underlying mechanisms are unknown. Here we show that the extracellular (␣) chain of LRP1 mediates TGF␤-induced enhancement of Wnt5a, which limits intracellular cholesterol accumulation by inhibiting cholesterol biosynthesis and by promoting cholesterol export. Moreover, we demonstrate that the cytoplasmic (␤) chain of LRP1 suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…2 E ) revealed increases in carnitine O-palmitoyltransferase 1 (CPT1A), a rate-limiting enzyme of fatty acid oxidation, that was not observed at the gene expression level (Fig. 2 D , CPT1), and prolow-density lipoprotein receptor-related protein 1 (LRP1), which plays a key role in cholesterol biosynthesis (29), HDL secretion from hepatocytes (30), and the removal of atherogenic lipoproteins, including VLDL (31). The proteomic analysis also identified a decrease in histidine triad nucleotide-binding protein 1 (HINT1), which – based on data from Hint-1 -deficient mice – is expected to contribute to reductions of total and esterified cholesterol (32).…”
Section: Discussionmentioning
confidence: 99%
“…2 E ) revealed increases in carnitine O-palmitoyltransferase 1 (CPT1A), a rate-limiting enzyme of fatty acid oxidation, that was not observed at the gene expression level (Fig. 2 D , CPT1), and prolow-density lipoprotein receptor-related protein 1 (LRP1), which plays a key role in cholesterol biosynthesis (29), HDL secretion from hepatocytes (30), and the removal of atherogenic lipoproteins, including VLDL (31). The proteomic analysis also identified a decrease in histidine triad nucleotide-binding protein 1 (HINT1), which – based on data from Hint-1 -deficient mice – is expected to contribute to reductions of total and esterified cholesterol (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, El Asmar and colleagues further investigated the molecular mechanism by which LRP1 controls ABCA1 expression [47**]. In this study, the second NPXY motif within the cytoplasmic tail of LRP1 was found to be important for LRP1-mediated expression of ABCA1 .…”
Section: Ldlr-related Protein 1 (Lrp1)mentioning
confidence: 90%
“…Atherosclerosis is a chronic condition characterized by impairments in three major processes: systemic and cellular cholesterol homeostasis, inflammation, and apoptosis/efferocytosis ( Libby et al, 2011 ). Essential roles for the multifunctional transmembrane protein LDL receptor-related-protein 1 (LRP1) have been reported for each of these three processes ( Boucher et al, 2003 ; Boucher et al, 2002 ; El Asmar et al, 2016 ; Mantuano et al, 2016 ; Subramanian et al, 2014 ; Zhou et al, 2009a ; Zurhove et al, 2008 ). Together with LDLR, LRP1 regulates the clearance of circulating cholesterol-rich remnant proteins by hepatocytes ( Rohlmann et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%